Pengaruh Derajat Putaran Kontrol Gas Terhadap Hasil Kadar Air Kunyit Pada Alat Pengering Tipe Rak - Oky Adithya Indrawan, Retno Eka Pramitasari (Universitas Hasyim Asy'ari, 2021)
Turmeric is one of the most commonly encountered rhizome plants that are used for cooking because it is a natural coloring of a food. Turmeric has a water content of about 80% to 82,5%. Drying is the process of heat transfer that is done to remove the water content in an object with a medium in the form of hot air. Currently there are 2 commonly used drying methods, namely drying in a natural way that uses solar heat as its heat media and artificial drying that uses other aids as heat media. This study used this type of experimental research with variations in the degree of gas control rotation of 90°, 135°, 180° on rack-type dryers. The purpose of this study is to find out whether or not the effect of the degree of gas control spin on the water content of turmeric evaporated. The results of the study will be conducted multiple regression analysis by conducting a T test on the SPSS 26 application. Results obtained from the T test stated a significance value of 0,015 < 0,05 and a calculated T value of 3,378 > 2,447. Conclusions obtained from the results of the T test stated the effect of the degree of gas control round on the evaporated turmeric water content.